(untitled) (International Journal of Physiotherapy, 2016)
Background: Rigid and kinesio tapings are commonly used in the rehabilitation of subacromial impingement syndrome (SIS). Yet; the effect of postural correction with the two taping materials in SIS has not been extensively studied. The purpose of the study is to examine the effect of postural correction with two different taping materials on scapular kinematics and electromyography of scapular upward rotators in patients with SIS. Methods: Twenty female patients with SIS participated in this study. Their age ranged from 30-60 years. Participants were randomly assigned into: Group I (Kinesio tape, n=10) and Group II (rigid tape, n=10). Thoracic and scapular taping with posture correction was applied to both groups. Scapular upward rotation at 0˚, 60˚, 90˚ and 120˚ of shoulder elevation and the activity level of the upper fibers of trapezius (UT), lower fibers of trapezius (LT) and serratus anterior (SA) muscles were measured before and immediately after taping application. Results: Both taping materials significantly increased scapular upward rotation at 60°, 90° and 120° angles (P =.004,.002 and .047 respectively) after the application of tape as compared to the before. In addition, significantly greater muscle activity of the LT and SA muscles (P =.027 and 0.05 respectively) were demonstrated by the kinesio-taping group as compared to rigid taping group during real taping condition. Conclusion: Both taping materials are effective in restoring scapular kinematics. Furthermore, kinesio taping has a facilitatory effect on the LT and SA muscles. Kinesio taping may be considered an alternative to rigid taping in patients with SIS.